Relationship between jealousy, emotional dependence and romantic love myths and dating violence in heterosexual college students - Guzmán-Toledo, Rosa María; Rojas-Solís, José Luis (Pensando Psicología, 2025)
Introduction: dating violence refers to behaviors that cause physical, sexual or psychological harm, committed by one of the members of the dyad, a problem considered a public health issue that makes no distinction of gender or sexual orientation. Objective: to analyze the relationship between the behaviors of romantic love myths, jealousy, emotional dependence and violence within university couple relationships. Method: this is an empirical study of non-experimental design, with cross-sectional and ex post facto approach; the sample was selected non-probabilistically and by convenience, thus 589 young Mexicans with an average age of 21 (SD=3.34) participated, who answered an electronic form with three instruments: Romantic Love Myths Scale, Love Addiction Scale and Violence in Adolescents’ Dating Relationships Inventory (VADRI). Results: a gender difference was found in the idealization of love myth, as well as a positive correlation between jealousy and emotional dependence in the female sample, and positive relationships between suffering and perpetrating violence in males and females. Conclusions: there was a link between jealousy and emotional dependence in both sexes, a significant relationship between different types of violence, as well as its possible bidirectionality. In the predictive analyses, jealousy was the main explanatory variable in the violence suffered, while dependence and jealousy were the main explanatory variables for the perpetration of violence.